(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2008)
The precious silver portrait of Lucius Verus, now in the Museo di Antichità in Torino, was found at Marengo (Alessandria) together with other broken silver objects. The treasure was probably hidden in the 3rd century A.D. and nobody has ever been able to return to collect it.The portrait depicts Lucius Verus wearing cuirass and military cloak, as he has always been shown in many portraits in the years before his death.The Marengo portrait is the most impressive piece of an important class of imperial busts worked in silver foil and decorated in relief. Probably the silver portraits of this group should have been displaced in public places, as tribunals or official palaces or castra, in order to represent the power and the majesty of the emperors. Some silver portraits were also dedicated on occasion of imperial celebrations by single officials or powerful people or members of a collegium.